Self-assembling Peptides (SAPs) as Powerful Tools for the Preparation of Antimicrobial and Wound-Healing Nanostructures - Dimmito, Marilisa P.; Marinelli, Lisa; Cacciatore, Ivana; Valeri, Anna Lucia; Rapino, Alessandra; Di Stefano, Antonio (Letters in Drug Design & Discovery, 2024)
Supramolecular self-assembly (SA) is a naturally occurring and free energy-driven process of molecules to produce nanostructured systems depending on the assembling environment. SA molecules have captivated the research attention since they possess singular physicochemical properties that are potentially useful to make the nanostructures quite suitable for biomedical applications, such as diagnostics, drug delivery, tissue engineering, and regenerative medicine. Due to their high biological activity and low toxicity, the self-assembly properties of peptides bid certain advantages as drugs and drug delivery platforms. Among the discovered self-assembling bioactive peptides (SAPs), antimicrobial peptides (AMPs) are widely distributed through plant and animal kingdoms and play a key role as an alternative strategy to fight infections bypassing conventional antimicrobial drugs, susceptible to antimicrobial resistance. Based on this evidence, in this review, we summarized the mechanism of the self-assembling of peptides, the main forces responsible for the SAPs formation, and the studies regarding their possible implication in infectious diseases as well as wound dressing materials.
Keywords: wound healing-promoting peptides